Effect of various manifold absolute pressures and air flowrates on throttle body injection mixer in compressed natural gas motorcycle - Chang, Siu Hua; Yaacob, Zulkefli; Mohsin, Rahmat (Faculty of Chemical & Natural Resources Engineering, UTM, 2007)
After being besieged by dilemmas related to mixing homogenenity and air-fuel ratio control of the former air fuel mixers [1,2], a new air-fuel mixer called Throttle Body Injection Mixer (TBIM), which is of electronic fuel controlled, was developed. To study the mixing characteristics of TBIM, effect of various manifold absolute pressures (MAPs) and air flowrates (Qa) on TBIM need to be determined. Therefore the objective of this work is to study the effect of various MAPs and Qa on the TBIM in a compressed natural gas (CNG) motorcycle through both the experimental work and Computational Fluid Dynamics (CFD) modeling. Experimental work was first carried out to investigate the MAPs at varying throttle angles for several engine speeds, followed by the corresponding Qa, which was attained through CFD modeling. The findings obtained were then verified through literature support. It was found that both the MAPs and Qa obtained exhibited a good agreement in the trending of graphs with the former works [3,4,5].